Small interfering RNA delivery to the neurons near the amyloid plaques for improved treatment of Alzheimer׳s disease - Qian Guo; Xiaoyao Zheng; Peng Yang; Xiaoying Pang; Kang Qian; Pengzhen Wang; Shuting Xu; Dongyu Sheng; Liuchang Wang; Jinxu Cao; Wei Lu; Qizhi Zhang; et al. (Elsevier, 2019)
Gene therapy represents a promising treatment for the Alzheimer׳s disease (AD). However, gene delivery specific to brain lesions through systemic administration remains big challenge. In our previous work, we have developed an siRNA nanocomplex able to be specifically delivered to the amyloid plaques through surface modification with both CGN peptide for the blood-brain barrier (BBB) penetration and QSH peptide for β-amyloid binding. But, whether the as-designed nanocomplex could indeed improve the gene accumulation in the impaired neuron cells and ameliorate AD-associated symptoms remains further study. Herein, we prepared the nanocomplexes with an siRNA against β-site amyloid precursor protein-cleaving enzyme 1 (BACE1), the rate-limiting enzyme of Aβ production, as the therapeutic siRNA of AD. The nanocomplexes exhibited high distribution in the Aβ deposits-enriched hippocampus, especially in the neurons near the amyloid plaques after intravenous administration. In APP/PS1 transgenic mice, the nanocomplexes down-regulated BACE1 in both mRNA and protein levels, as well as Aβ and amyloid plaques to the level of wild-type mice. Moreover, the nanocomplexes significantly increased the level of synaptophysin and rescued memory loss of the AD transgenic mice without hematological or histological toxicity. Taken together, this work presented direct evidences that the design of precise gene delivery to the AD lesions markedly improves the therapeutic outcome. KEY WORDS: siRNA delivery, Neurons, Amyloid plaques, BACE1 gene, Alzheimer׳s disease